The Description of Family Functioning in Mental Disorder - Aulia Alfafa Rizqa; Ah Yusuf; Rr Dian Tristiana (Universitas Airlangga, 2020)
Introduction: Marriage with a spouse who has a mental disorder is not easy. Many couples divorce when married with mental disorder patients because they feel difficulties in their marital relationships, but some of them can maintain it for years. The purpose of this research is to describe family functioning in mental disorders.Method: The design of this study was cross-sectional. The sample was 31 wives of people with mental disorder and they were obtained using an accidental sampling technique. The instrument of this research are Family Assessment Device and The Investment Model Scale then analyzed with Pearson correlation test (Î± < 0,05).Results:Â The family functioning in mental disorders who were in the low category are 4 families (12.9%), 21 families (67.7%) are in the sufficient category, and 6 other families (19.4%) are in the high categoryConclusion:Â Family functioning in mental disorder was not worked effectively in maintaining a balance in the dimensions of problem-solving, communication, family roles, affective responsiveness, affective involvement, and behavior control.